Dealing with perioperative antiplatelet treatment for transurethral resection of the bladder: primum non nocere - Audenet, François; Sfakianos, John P. (Translational Andrology and Urology; Vol 7, Supplement 2 (May 28, 2018): Translational Andrology and Urology, 2018)
The number of patients receiving antithrombotic treatment is increasing (1), thus increasing the number of patients under anticoagulant or antiplatelet treatment scheduled to undergo endo-urology surgery.